Investigating student perceptions of learning assistants - Coghlan, Virginia M. (Kansas State University, 2019)
Learning assistant (LA) programs have supported course transformations and active learning at more than 85 different institutions over the past 16 years. The Physics Department at Kansas State University initiated an LA program in its calc-based, introductory physics courses in 2017. Pairs of LAs began to replace one Teaching Assistant (TA) per studio section as secondaries, working alongside a primary instructor, usually a faculty member or instructor. This program is still in transition, so each semester some studios have LAs and some have a TA. We conducted interviews with students who experienced a combination of LAs and TAs in their two semesters of introductory physics. We wanted to know what their perceptions were of these secondary instructors in order to identify possible explanations for why LAs are successful in increasing student learning and identify areas for future exploration. We found that while students did not seem to be aware of an explicit difference between their TAs and LAs, they responded more positively to their LA's preparation and closeness to the course, to interactions that relate to LAs pedagogy training, and to an ease of building relationships with their LAs. Students also noticed that their LAs had less relative expertise and could sometimes be too laid back in their interactions.
Keywords: Physics; Education; Learning Assistant; Teaching Assistant; Phenomenography; Student Perceptions